2018
DOI: 10.1051/0004-6361/201833040
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas content in obscured AGN at z > 1

Abstract: Aims. The standard active galactic nuclei (AGN)-galaxy co-evolutionary scenario predicts a phase of deeply "buried" supermassive black hole growth coexisting with a starburst (SB) before feedback phenomena deplete the cold molecular gas reservoir of the galaxy and an optically luminous quasar (QSO) is revealed ("SB-QSO evolutionary sequence"). The aim of this work is to measure the cold gas reservoir of three highly obscured QSOs to test if their gas fraction is similar to that of submillimeter galaxies (SMGs)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 221 publications
11
71
2
Order By: Relevance
“…The presence of an AGN can influence the measurement of the stellar mass of the galaxy and artificially lower the calculated gas fraction of the galaxies. This result is consistent with the findings of Perna et al (2018) who found systematically low gas fractions in obscured AGN at z > 1 and suggests that AGN feedback could lead to the expulsion of gas. One of these galaxies has a low gas fraction (21%) and does not show any sign of an AGN.…”
Section: A Large Fraction Of Galaxies In Our Sample With Low Gas Fractionssupporting
confidence: 92%
“…The presence of an AGN can influence the measurement of the stellar mass of the galaxy and artificially lower the calculated gas fraction of the galaxies. This result is consistent with the findings of Perna et al (2018) who found systematically low gas fractions in obscured AGN at z > 1 and suggests that AGN feedback could lead to the expulsion of gas. One of these galaxies has a low gas fraction (21%) and does not show any sign of an AGN.…”
Section: A Large Fraction Of Galaxies In Our Sample With Low Gas Fractionssupporting
confidence: 92%
“…Both theoretical simulations and observational studies suggest a link between the growth of galaxies and their supermassive black holes (SMBHs, M BH =10 6 -10 9 M  , e.g., Hopkins et al 2008;Ishibashi & Fabian 2016). Under this paradigm, starburst-dominated galaxies and the active galactic nuclei (AGNs) dominated QSOs are essentially the same systems observed at different evolutionary stages (e.g., Sanders et al 1988;Perna et al 2018). Therefore, surveying the AGN activity in the SMG population provides insights into not only SMBH growth, but also potentially the evolutionary cycle of massive galaxies.…”
Section: Agn Fractionmentioning
confidence: 99%
“…The detection of powerful multi-phase galactic-scale outflows shows that AGNs are capable of removing large amounts of gas from their host galaxies. As recently discussed by Perna et al (2018), neither the evolutionary sequence nor orientation effects with respect to the obscuring medium alone are able to explain the observed SFEs in obscured and unobscured AGNs.…”
Section: Discussionmentioning
confidence: 80%
“…For example, WISE has played an important role in selecting these hyperluminous objects, in combination with (e.g., Bischetti et al 2017) or without (Fan et al 2018) photometry from the SDSS. Other works focused on possibly less luminous objects that were still preferentially dust obscured (e.g., Polletta et al 2011;Banerji et al 2017;Kakkad et al 2017;Perna et al 2018), radio loud (e.g., Willott et al 2007), or on the highest redshifts detected in [C ii]λ158 µm (e.g., Venemans et al 2017). In turn, J0015+1842 is not particularly bright, with an i-band magnitude in only the second brightest quartile of SDSS quasars at the same redshift, for instance, and it is only moderately reddened (A V ∼ 0.3−0.4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation